Providing Employment Opportunities For Refugees in Indonesia : Positive And Negative Effects - Havez, Muhammad; Susanti, Susi; Ninin Ernawati (Department of Law, Faculty of Law, University of Mataram, 2023)
International refugee cases have always been a relevant topic for discussion because this topic still needs a solution. Indonesia, as a transit country, has optimally assisted refugees. However, refugees living in Indonesia still often complain that IOM's assistance has been inadequate and insufficient to meet family needs. This research discusses what the Indonesian government is doing to protect refugees. Furthermore, can the right to work for refugees be granted in Indonesia. This research concludes that the Indonesian government builds residences and provides educational, religious, and other facilities to asylum seekers. Granting the right to work for refugees can be given to asylum seekers, but they can only be given the right to work in the government sector as laborers. A concrete example is being a laborer on government tea plantations. They may be paid by the Indonesian government but are managed by the government and cannot freely determine the job they want.